Polypore funga and species diversity in tropical forest ecosystems of Africa, America and Asia, and a comparison with temperate and boreal regions of the Northern Hemisphere - Heng Zhao; Yingda Wu; Zhirong Yang; Honggao Liu; Fang Wu; Yucheng Dai; Yuan Yuan (Forest Ecosystems, 2024)
Polypores play a crucial role in energy recycling and forest regeneration in forest ecosystems. The majority of them are wood degraders; some are forest pathogens and others are ectomycorrhizal symbionts. The basidiocarps provide food and shelter for many organisms, mostly invertebrates, but also some vertebrates, as well as food and medicine for humans. Despite extensive research on the species diversity and phylogenetic relationships of polypores in recent years, there remains a lack of comprehensive understanding of their distribution patterns and species composition at the large scale. Checklists of polypores from the tropical zone, including tropical Africa, tropical America, and tropical Asia, were analyzed for species diversity, distribution patterns, major taxa, and nutritional modes. A total of 1,902 polypore species was found in the three regions, representing 8 orders, 46 families, and 250 genera of Agaricomycetes. The orders Polyporales (especially the family Polyporaceae) and Hymenochaetales (especially the family Hymenochaetaceae) had the most prolific taxa, with their species accounting for 93.4% of the total polypores listed. Each of 1,565 (or 82.3%) of the total 1,902 species were found in only one of the three regions studied, and we treat them temporarily as “regional endemic species”. Only 141 species were shared among all three regions, accounting for a mere 7.4%. Tropical Africa and tropical America had the greatest number of shared species and the highest Sørensen similarity index (SC) value. Tropical forests had a higher species richness compared with temperate to boreal forests of the Northern Hemisphere, and in addition, also a higher proportion of white rot polypores compared to brown rot and ectomycorrhizal species. This study outlines the distribution patterns and species diversity of polypores in the world, shedding light on their ecological significance in diverse ecosystems.